Levels of HIV/AIDS stigma and associated factors among sexually active Ethiopians: analysis of 2016 Ethiopian Demographic and Health Survey Data - Merga Belina Feyasa; Mamo Nigatu Gebre; Teshome Kabeta Dadi (BMC, 2022)
Abstract Background Stigma and discrimination have fueled the transmission of the disease and dramatically increased its negative public health impact. Even though the disease has extremely ravaged human life, stigma, and discrimination attached to it are not well addressed in Ethiopia at the country level. The reduction of stigma and discrimination in a population are important indicators of the success of programs that target HIV prevention and control. This study aimed to assess the level of HIV-related stigma and its determinants among sexually active Ethiopians. Methods A public domain data were obtained from 2016 Ethiopian Demographic and Health Survey in which two-stage cross-sectional stratified cluster sampling was applied. A total of 28,371 sexually active Ethiopians were interviewed from both rural and urban parts of Ethiopia. Descriptive Statistics and multilevel ordinal logistic regression (proportional odds model) were used to summarize data and to investigate correlates of HIV-related stigma. Results Only 5.1% (95% CI: 4.5%, 5.8%) of sexually active Ethiopians did not have a stigmatizing attitude, whereas, 59.2% (95% CI: 57.3%, 61.1%) and 35.65% (95% CI: 33.5%, 37.9%) of them had a moderate and high level of stigma respectively. Regression results show that residence (AOR = 1.82, 95% CI:1.46, 2.27), education (AOR = 0.65,95% CI: 0.50,0.84), owning mobile (AOR = 0.63,95% CI:0.55,0.72), HIV-testing (AOR = 0.77, 95% CI:0.70,0.84), age (AOR = 0.81, 95% CI: 0.73, 0.91), religion (AOR = 1.53,95% CI:1.33,1.76), and marital status (AOR = 1.38, 95% CI:1.19, 1.61) were significantly associated with HIV-related stigma (p < 0.0001). Conclusion Regardless of all efforts put in a place to prevent and control HIV, a significant proportion of sexually active Ethiopians have stigmatizing attitudes. Residence, educational level, owning mobile, HIV test uptake, age, religion, and marital status were determinants of HIV-related stigma. Expanding mobile coverage, promoting HIV counseling and tests, promoting HIV education, and working with religious leaders, among other strategies could be used to minimize the stigma attached to the disease to best prevent and control it.